Downregulation of tumor suppressor RACK1 by Helicobacter pylori infection promotes gastric carcinogenesis through the integrin β-1/NF-κB signaling pathway - Hu, Yi; Liu, Jian-Ping; Li, Xue-Yang; Cai, Yan; He, Cong; Li, Nian-Shuang; Xie, Chuan; Xiong, Zhi-Juan; Ge, Zhong-Ming; Lu, Nong-Hua; Zhu, Yin (Cancer letters, 2019)
Receptor of activated protein kinase C 1 (RACK1) is downregulated in gastric cancer and is involved in modulating NF-κB signaling pathway activity. However, the underlying molecular mechanisms regulating RACK1 expression are unclear. In this study, we demonstrated that downregulated expression of RACK1 was observed in gastric cancer tissue compared to adjacent normal tissue and was correlated with poor prognosis in patients. Helicobacter pylori (H. pylori) infection downregulated RACK1 expression in concert with canonical NF-κB signaling pathway activation in vivo and in vitro. RACK1 overexpression suppressed NF-κB signaling pathway activation as well as the release of downstream proinflammatory cytokines. In addition, RACK1 downregulation increased integrin β-1 expression, while integrin β-1 silencing decreased NF-κB signaling activation. Moreover, H. pylori infection downregulated RACK1 but upregulated integrin β-1 expression at the precancerous lesion stages in human subjects. Our data indicate that H. pylori infection promotes the upregulation of integrin β-1 expression via downregulation of RACK1 expression, which subsequently leads to the elevated activation of the NF-κB signaling pathway, an essential step in H. pylori-induced carcinogenesis. •RACK1 is downregulated in GC tissues and is associated with poor prognosis in GC patients.•H. pylori infection downregulated RACK1 and activated the NF-κB signaling pathway in vitro and in vivo.•RACK1 negatively regulated H. pylori infection-induced NF-κB activation by modulating integrin β-1.•H. pylori downregulated RACK1 expression but upregulated integrin β-1 and p-P65 (Ser 536) expression in human subjects.